ATTITUDE TO NATURE AND PREVENTION OF ENVIRONMENTAL PROBLEMS (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article analyzes the attitude towards nature and modern problems of its protection from a scientific point of view. In the modern period, as a result of the rapid growth of productive forces in society, as a result of the extensive use and exploitation of nature, the ecological balance has been disrupted and environmental tension has arisen. Disturbance of the ecological balance is expressed in pollution of the atmosphere, groundwater, seas and oceans, solid waste, noise, strong exposure to radioactive substances, etc. To prevent it, it was justified that man must acquire special importance and treat nature properly.